The worldview for sustainable cities and communities - Zamudio, Rodrigo (Universidad de Lima. Carrera de Arquitectura, 2021)
DOI: https://doi.org/10.26439/limaq2021.n007.5182 Bringing the natural closer to citizens can strengthen and consolidate a sense of belonging to the ecosystem that surrounds them. This situation occurs in indigenous communities such as the Ashaninka, in which protecting the environment is linked to survival. It is necessary to understand the characteristics of a space as a place that houses living beings, which are conditioned to the environment where social and economic systems are found. Therefore, linking these aspects is important to find human well-being within a balanced ecosystem.